Depression promotes hepatocellular carcinoma progression through a glucocorticoid-mediated upregulation of PD-1 expression in tumor-infiltrating NK cells. (4th February 2019) - Zhao, Yawei; Jia, Yong; Shi, Tongfei; Wang, Wencong; Shao, Dan; Zheng, Xiao; Sun, Madi; He, Kan; Chen, Li
Abstract: There is a growing belief that depression was positively associated with the progression of liver cancer. However, the driving molecular events behind the depression in liver cancer are poorly understood and need to be elucidated. Since hyperactivity of the hypothalamic–pituitary–adrenal axis during depression leads to the excessive release of glucocorticoids (GCs), which suppress the activity of natural killer (NK) cells, we hypothesized that high levels of GCs during depression may inhibit function of tumor-infiltrating NK cells during the progress of the liver cancer. Using chronic unpredictable mild stress-induced depressed mice model, we showed that the progression of liver cancer was significantly accelerated in the depressed mice. The high levels of GCs were observed in both depressed mice and depressed patients with liver cancer. Importantly, the expression of programmed death (PD)-1 on NK cells was specifically increased in the tumor microenvironment rather than that in blood or spleen. Coculture studies demonstrated that the expression of PD-1 was significantly increased and cytotoxicity of NK92 cells was remarkably decreased by the dexamethasone treatment through PD-L1-dependent pathway. To the best of our knowledge, we first found that PD-1/PD-L1-mediated exhaustion of infiltrated NK cells promoted hepatocellular carcinoma progression under depression and provided a novel strategy for GC-mediated antidepressant therapy in patients with liver cancer. Abstract : The excessive release of glucocorticoids during depression can inhibit the function of tumor-infiltrating NK cells during the progress of the liver cancer and thus promote the progression of hepatocellular carcinoma.